Study guides

☆☆

Q: 2x3 plus 8x3-5x2 plus 8x2

Write your answer...

Submit

Still have questions?

Related questions

What are the factors? 2x3 - 8x2 + 6x = 2x(x - 1)(x - 3).

2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.

8x2 + 16x + 8 = 0

8x2 + 6x - 9 = (2x + 3)*(4x - 3)

8x2 + 2x - 1 = (4x - 1)(2x + 1).

8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)

the roots are 1, - 1/3, - 3 1/2 and 3 1/2

7Improved Answer:8x2-18x+9 = (4x-3)(2x-3)

8x2+6x-35 = (2x+5)(4x-7) when factored

8x2(x + 3)

x=5

(2x + 1)(4x + 7)

People also asked